Avaliação da estabilidade aeróbia de silagens de milho - Silva, Michele Simili da (2009)
The objective was to evaluate the main factors influencing the quality and aerobic stability of silage corn and to seek the most viable techniques for determining their density. Two experiments were carried out and in the first it was evaluated the effect of plastic tarp to protect the characteristics of the silo panel corn silage during the use, where half of the panel was covered with canvas and the other half was kept discovery. Each part of the panel was divided into three vertical strata: stratum superior, median and basal panel of the silo. The content of dry matter (DM) in the panel that was protected with black tarp was higher than the part without protection, with averages of 30.92 and 32.26% of DM respectively. The values of organic matter (OM) and non-structural carbohydrates (NSC) observed in the upper stratum of the silo panel with and without protection, were lower (p <0.05) to the values found in the median and basal layers. The populations of filamentous fungi and yeasts were not different (p> 0.05) between the halves of the panel and strata studied. The lowest values of density and resistance to cone penetration of metal were found in superficial layer, which differed statistically from the other strata. The use of black plastic tarp for protection of the silo during the use of corn silage contributes to the increase of temperature in the silo panel, not favoring the aerobic stability of corn silage. The Second Experiment assessed the effect of inoculant bacterial enzyme and the height of cut on the aerobic stability of silage maize. There were evaluated the following silages: cutting height of 20 cm without addition of inoculant, cutting height of 40 cm without the addition of inoculant, cutting height of 20 cm with inoculant and cutting height of 40 cm with the addition of inoculant. Each silo was divided into three vertical strata: stratum superior, median and basal panel of the silo. The inoculum and bacterial enzyme-cutting height of xv corn showed no effect on the population of filamentous fungi and yeast from silage. The addition of inoculant to the maize plant with the cutting height of 20 cm resulted in silages with higher values of pH. Corn silage with cutting height of 40 cm with enzyme-bacterial inoculant, showed the lowest specific masses and higher temperatures. In the two experiments the relationship between the penetration resistance of the metal cone and the mass was specified as an alternative to estimate indirectly the silage density to replace the traditional methods. It was concluded that the penetrometer can be used as indirect method to determine the density of silage maize, since the correlation between density and estimated density values were high and positive.